Implementation of Fuzzy Inference System With Tsukamoto Method for Study Programme Selection - Fenty Ariani; Robby Yuli Endra (Bandar Lampung University (UBL), 2013)
Deciding study programme is crucial because any fault in making the decision will affect students’ learning motivation, length of study period which exceeds the standard, and the students’ failure. With a methodical selection of study programme, each student is expected to focus on his interest and capability more. Fuzzy Inference System (FIS) with Tsukamoto method can be applied to support the settlement. In the method, output is obtained with four stages, namely the formation of fuzzy sets, the establishment of rules, the application of implicated functions, and defuzzification. The purpose of this study is to apply FIS with Tsukamoto method to the decision of study programme which fits prospective students’ interest and capability. Moreover, the input variables involve Interview Scores, Scores of Informatics Engineering, Scores of Information Systems and Scores of Written Tests. Output variables are the students’ interest either in the Department of Informatics Engeenering or the Department of Information System